Examining the Determinants of Students’ Entrepreneurial Intention and Behavior: SEM-PLS Analysis - Ananda Setiawan; Ratna Yulianti (Economics Education Department Universitas Negeri Semarang, 2025)
This study aims to analyze the effects of curriculum attendance, subjective norms, and perceived behavioral control on students’ entrepreneurial intention and behavior. A quantitative approach was employed, utilizing Structural Equation Modeling based on Partial Least Squares (SEM-PLS) to examine the relationships among the variables. The sample consisted of 292 students who had already operated or were in the process of starting a business. Data were collected using an e-questionnaire distributed via social media platforms. The results indicate that curriculum attendance does not have a positive effect on entrepreneurial intention. In contrast, subjective norms and perceived behavioral control have positive and significant effects on entrepreneurial intention. Furthermore, curriculum attendance, subjective norms, perceived behavioral control, and entrepreneurial intention all have positive and significant effects on entrepreneurial behavior. These findings underscore the importance of strengthening practice-based entrepreneurship curricula, fostering a supportive social environment, and enhancing students’ self-efficacy in promoting the development of independent and competitive young entrepreneurs.